Airway remodeling in children with asthma, which runs on the background of intracellular infections - Chernyshova O.E.; Abaturov A.E. (Medičnì Perspektivi)
The paper provided information on the impact of persistent intracellular infections, including cytomegalovirus, caused by herpes simplex virus I / II types, Epstein-Barr virus, Сhlamydophila pneumoniae and Mycoplasma pneumoniae, on airway remodeling process in the form of smooth muscle hypertrophy, enhanced formation of new vessels, epithelial cell hyperplasia, collagen deposition, sealing of the basement membrane in bronchial asthma in children. Changes of matrix metalloproteinases, tissue inhibitor of matrix proteases, transforming growth factor, autoantibodies to collagen type III, endothelin-1 in patients with asthma and their influence on the processes of morphological adjustment of airways, which lead to deterioration of the disease course in children are described. The data obtained call the need of etiopathogenetic treatment along with the basic treatment aimed to reduce airway remodeling, which enables to decrease asthma severity and reduce disability.